‘Videography as performance’ in the service of social movement visibility and interaction amidst the pandemic: the case of the support art workers initiative in Greece - Constandinides, Costas; Papa, Venetia; Ioannou, Maria (My University, 2024)
This study aims to contribute to scholarship on online video activism by looking at mobilization videos created by the Support Art Workers (SAW) movement which emerged during the COVID-19 crisis in Greece. Our main observation is that several SAW videos consist of an assemblage of performance art elements and protest visuals which together with expressive uses of video production exemplify a “videography as performance” approach. We examine three SAW mobilization videos as a type of “activist video as performance,” which, aside from their function as invitations to protest-events, also form an innovative means of encouraging active civic engagement. Furthermore, we argue that aspects of the performance art elements and protest imagery included in the videos speak back to previous protest trajectories in Greece. Our overall objective is to show how SAW’s communication tactics have shaped new ways of visualizing protest goals that expand existing paradigms of online activist video.
Keywords: Online video activism; Support art workers movement; Videography; Greece; Mobilization; Performance